MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR MUATAN IPS MENGGUNAKAN MODEL PELANGI DI SEKOLAH DASAR - Rohana; Sari, Raihanah; Fathul Jannah; Akhmad Riandy Agusta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem of this research is the low level of critical thinking skills and student learning outcomes in social studies content. The solution to overcome this problem is to use the PELANGI model in the learning process. The aim of this research is to analyze critical thinking skills and student learning outcomes in social studies content. This research used a qualitative and quantitative approach with the type of classroom action research (PTK) and was carried out in 3 meetings. This research was carried out in class IV at SDN Hilir Mesjid which consisted of 11 students. The research results show that critical thinking skills obtained a percentage of 82% with the criteria "very skilled" and student learning outcomes with a percentage of 91% with the criteria "complete". Based on the data and results of this research, it can be concluded that the application of the PELANGI model (Problem Based Learning, Think Pair Share, Talking Stick) can help improve critical thinking skills and have a good impact on student learning outcomes